ECONOMIC AND SOCIAL FACTORS RELATING TO POTATO FARMERS' DECISIONS IN OBTAINING FINANCE FROM MIDDLEMEN IN KERTASARI SUB-DISTRICT, BANDUNG DISTRICT - Rafa Thea Kirana Saufika; Eliana Wulandari (Universitas Tadulako, 2021)
The availability of financial institutions remains low in Kertasari Sub-District, causing farmers to be unable to optimally utilize financial institutions to borrow capital for farming activitiy. As funding provider, informal institutions are considered to be relatively flexible and easy to access because of uncomplicated administrative procedures compared to formal financial institutions which unfortunately are often seen as much more convenient to use for the farmers. The purpose of this study was to analyze the factors that relate to potato farmers' decisions in obtaining finance from middlemen in Kertasari Sub-District, Bandung District. The study design is quantitative research using survey method. The data was analyzed using logistic regression. The results showed that there were several factors that related to farmers' decisions in obtaining finance from middlemen, including farming expenses and farm income.